The scientific elucidation of daodi medicinal materials - Xindan Liu (Chinese Medicine, 2020)
Abstract Daodi medicinal materials (DMMs), with unique characteristics and specific ecological growing environments, are recognized as high-quality medicinal products of Chinese medicinal materials (CMMs). The quality evaluation of CMMs is fundamental for standardization. The concept and application of DMMs have a long history as described in records in ancient books and rooted in practice and experience over generations. DMM is the specific term for pure, superior medicinal herbs with the following characteristics: optimum harvest season (reflecting the appropriate developmental stage of the plant), scrupulous processing, traditional preparation technology, etc. As DMM and high-quality medicinal products are traditionally thought to be closely related, modern scientific studies that confirm the association of these products are described. This article aims to clarify the scientific elucidation of DMMs.